2022
DOI: 10.1523/jneurosci.1176-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Intercalated Cells: Gate Keepers and Conveyors of Internal State to the Circuits of Emotion

Abstract: Generating adaptive behavioral responses to emotionally salient stimuli requires evaluation of complex associations between multiple sensations, the surrounding context, and current internal state. Neural circuits within the amygdala parse this emotional information, undergo synaptic plasticity to reflect learned associations, and evoke appropriate responses through their projections to the brain regions orchestrating these behaviors. Information flow within the amygdala is regulated by the intercalated cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 129 publications
0
7
1
Order By: Relevance
“…Indeed, even in juvenile mice prenatally exposed to PLX3397 which display more transient lesions, we observed a disorganization of an axonal tract abutting the CSA, a capsule that conveys inputs to the Am, an essential brain structure which dysregulation is linked to neurodevelopmental disorders. 73 , 74 , 75 Both axonal tracts and Foxp2-positive inhibitory interneurons, important to gate inputs to the Am, 76 , 77 , 78 were disorganized ( Figures S6 A and S6B). Electrophysiological slice recordings in adult mice revealed that morphological deficits correlated with a consistent imbalance of inhibition/excitation (I/E) responses of Am pyramidal neurons following capsule stimulation ( Figure S6 C).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, even in juvenile mice prenatally exposed to PLX3397 which display more transient lesions, we observed a disorganization of an axonal tract abutting the CSA, a capsule that conveys inputs to the Am, an essential brain structure which dysregulation is linked to neurodevelopmental disorders. 73 , 74 , 75 Both axonal tracts and Foxp2-positive inhibitory interneurons, important to gate inputs to the Am, 76 , 77 , 78 were disorganized ( Figures S6 A and S6B). Electrophysiological slice recordings in adult mice revealed that morphological deficits correlated with a consistent imbalance of inhibition/excitation (I/E) responses of Am pyramidal neurons following capsule stimulation ( Figure S6 C).…”
Section: Resultsmentioning
confidence: 99%
“…Important findings in this work include what was not observed. For instance, projections from the BLA to the ITCs is a commonly discussed synapse in ITC field (Asede et al, 2022, Palomares-Castillo et al, 2012, however our rabies tracing showed very little input from the BLA to ITCs, indicating that this connection reflects a minor subpopulation and that the ITCs likely serve broader functions than currently known or suggested. Instead, based on density of presynaptic regions, ITCs are more likely driven by cortical and thalamic nuclei that may present an unremarked confound in BLA-ITC studies.…”
Section: Discussionmentioning
confidence: 57%
“…Since mice rely heavily on olfaction to navigate their environment, olfactory areas are expected to play an important role in social recognition. The IA consists of clusters of GABAergic neurons surrounding that basolateral nuclear complex (BNC) of the amygdala which are thought to mediate fear extinction by inhibiting amygdalar outputs to the hypothalamic and brainstem circuits [76][77][78]. These IA neurons receive excitatory inputs from the infralimbic cortex (IL) and BNC that presumably activate this fear extinction circuit [79].…”
Section: Discussionmentioning
confidence: 99%